Microstructure features and mechanical/electrochemical behavior of directionally solidified Al−6wt.%Cu−5wt.%Ni alloy - RODRIGUES, Adilson Vitor; LIMA, Thiago Soares; VIDA, Talita Almeida; BRITO, Crystopher [UNESP]; GARCIA, Amauri; CHEUNG, Noé (Elsevier, 2021)
The effects of the addition of 5.0 wt.% Ni to an Al−6wt.%Cu alloy on the solidification cooling rate T˙ growth rate (VL), length scale of the representative phase of the microstructure, morphology/distribution of intermetallic compounds (IMCs) and on the resulting properties were investigated. Corrosion and tensile properties were determined on samples solidified under a wide range of T˙ along the length of a directionally solidified Al−6wt.%Cu−5.0wt.%Ni alloy casting. Experimental growth laws were derived relating the evolution of primary (λ1) and secondary (λ2) dendritic spacings with T˙ and VL. The elongation to fracture (δ) and the ultimate tensile strength (σU) were correlated with the inverse of the square root of λ1 along the length of the casting by Hall−Petch type experimental equations. The reinforcing effect provided by the addition of Ni in the alloy composition is shown to surpass that provided by the refinement of the dendritic microstructure. The highest corrosion resistance is associated with a microstructure formed by thin IMCs evenly distributed in the interdendritic regions, typical of samples that are solidified under higher T˙.
Keywords: Al−Cu−Ni alloys; as-cast microstructures; corrosion resistance; dendritic spacings; tensile properties